Secret sharing scheme for key management of secure data sharing in cloud - Abd Majid, Noorhafezan (2019)
Cloud computing is no longer a new phenomenon in the industry. Cloud storage is an important milestone in the cloud computing industry and one of the security features that were introduced in cloud storage is via cryptographic methods to control the access only to authorized users. One of the known issues in cloud storage is the high key generation time for large-scale users and limiting the use of cryptography for data encryption. This problem can be overcome by using cryptography uses a single key, but another problem will arises is the potential for a single point of vulnerability if the key fell in the hands of unauthorized persons, then the whole secret and information can be compromised. The objectives of this study were to execute and analyze key generation times for large-scale users using the AES-256 method and Shamir's Secret Sharing Scheme, which both are still using a single key concept and prove Shamir’s Secret Sharing Scheme is more suitable for large-scale users. Further testing proves that Shamir's Secret Sharing Scheme is more appropriate for large-scale users covering key generation and thresholds to ensure data is completely secure. There are five (5) phases for this study, identify problems and requirement analysis, design and analysis, design an algorithm, code development and result analysis, and documentations. The test run in localhost by using PHP platform and there are additional components such as the Composer for the implementation of Shamir's Secret Sharing Scheme and the comparison will be recorded based on the two data types, number of users and file size. Based on the results of the tests, it can be proved that Shamir's Secret Sharing Scheme provides key generation times faster than AES-256, and strengthen by the control of key threshold to ensure that the stored data is more secure. Shamir's Secret Sharing Scheme has also denied the problem of point the vulnerability exist in the AES-256.